2018
DOI: 10.1371/journal.pone.0195368
|View full text |Cite
|
Sign up to set email alerts
|

Do all infants need vitamin D supplementation?

Abstract: A high prevalence of vitamin D deficiency (VDD) in children has been observed worldwide, but there are few studies on the nutritional status of vitamin D (VD) in healthy infants. The main cause of deficiency in healthy children is breastfeeding without supplementation and lack or insufficiency of sun exposure. The aims of this study were to determine serum concentrations of 25(OH)D and verify its association with parathyroid hormone (PTH) concentrations and use of VD supplementation in healthy infants aged ≥ 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
(90 reference statements)
0
13
0
1
Order By: Relevance
“…Otherwise, vitamin D plays an important role in both the immune and cardiovascular systems, it is considered to be a kind of steroid hormone 6 . Several studies have revealed the high prevalence of poor vitamin D status in school-age children around the world 7 12 , and few studies investigated the nutritional vitamin D status of newborns 13 , 14 . The main reasons for low level of vitamin D in children are without supplementary feeding and lack of outdoor sun exposure 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, vitamin D plays an important role in both the immune and cardiovascular systems, it is considered to be a kind of steroid hormone 6 . Several studies have revealed the high prevalence of poor vitamin D status in school-age children around the world 7 12 , and few studies investigated the nutritional vitamin D status of newborns 13 , 14 . The main reasons for low level of vitamin D in children are without supplementary feeding and lack of outdoor sun exposure 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, no association was found between BMI values and free 25OHD levels. No uniform results have been reported in publications analyzing the relationship between BMI and total 25OHD concentrations in paediatric population [ 40 , 41 ]. As expected and commented above, the sustained administration of vitamin D supplements increased the circulating concentrations of free and total 25OHD.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the prevalence of children with Rickets between the ages of 8 to 24 months was 6%. On the other hand, the prevalence of vitamin D insufficiency was 30% in studies done Brazil and Pennsylvania was 30% and 16% respectively (Almeida et al, 2018;Michel et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Globally, Rickets prevalence is increasing and many children were affected by this illness. It mostly affects infant and the prevalence among them vary from 2.7% and 45% (Almeida et al, 2018). According to a studies conducted in Canada and in New Zealand the incidence rates of rickets among children was 2.9 and 10.5 per 100 000 respectively (Ward, Gaboury, Ladhani, & Zlotkin, 2007;Wheeler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%